The effect cooling media in pack carburizing quenching on the corrosion resistance of ASTM A36 steel - S. Sujita; P. Padmiatmi; A. Zainuri; R. Sutanto (Dinamika Teknik Mesin, 2025)
Rotary plow on hand tractor functions as a tool to plow the land efficiently in agricultural mechanization. This tool is made of ASTM A36 steel which functions to cut, chop, and turn the soil, thus improving the soil structure and preparing the land for planting. The disadvantages of ASTM A36 steel are lowÃ‚Â  impact toughness and corrosion resistance. In this study, ASTM A36 steel was pack carburizing quenching, with variations in cooling media in the form of water, coconut oil , and SAE 40 oil. The results of the studythe use of coconut oil as a cooling medium in the pack carburizing quenching process of ASTM A36 steel cause lower corrosion rates, slower cooling rates so that energy and impact toughness are higher compared to water as a cooling media So that coconut oil as a cooling media can be applied to the pack carburizing quenching rotary plow process to increase corrosion resistance.